Optimalisasi Peran Guru dalam Mengembangkan Kemampuan Membaca Siswa Sekolah Dasar Kelas Rendah - Dwinda Darapati; Adrias Adrias; Salmaini Syafitri Syam (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to discuss the difficulties faced by lower-grade elementary school students in reading, and to reveal the efforts made by teachers to improve the reading skills of lower-grade students in three elementary schools in Nagari III Koto across three different grade levels. Through this descriptive qualitative research method, various efforts made by teachers to enhance the reading ability of lower-grade elementary students are identified and analyzed. The characteristics indicating reading difficulties among lower-grade students include stuttering while spelling, lack of vocabulary knowledge, difficulty in combining words with affixes, and an inability to recognize vocabulary properly. Teachers employ various strategies, such as providing extra study time, assigning homework that allows students to practice daily even outside of school, and offering motivation. Other strategies include individualized guidance, forming study groups, and creating engaging and diverse learning experiences to increase students' interest in reading. Furthermore, parental involvement plays a crucial role in children's reading abilities. Economic conditions often become a reason why parents rarely dedicate time to their children's reading development, thereby affecting their reading skills.